TERAPI DENYUT ITRAKONAZOL PADA KASUS TINEA UNGUIUM - Sujana, Kadek Yuda; Darmada, IGK; Rusyati, Luh Made Mas (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana, 2014)
Dermatophytosis is a superficial fungal infection on skin, hair, and nail which caused by dermatophyt. Onicomycosis refers to nail infection which caused by fungal dermatophyt, fungal nondermatophyt, or yeast. Dermatophyt that infected the nail called tinea unguium. Diagnosis for tinea unguium based on the microscopic test with KOH 20%, culture Saboraud’s dextrose agar ( SDA ) and histopathologic. In this case reported male, 28 years old with changed of the color of nail since four years ago. Dermatologic states is located on ten hand’s fingers and ten foot’s fingers which looked like the nail is thickening, there are keratin debris on the distal part of nail with rough end and nail plate looked like picked up. KOH 20% test from nail’s scratch founded long hypha and branched. This patient gives treatment with Itraconazol dose 200 mg twice a day for one week in one month and repeated for three months. The prognosis is good.
Keywords: tinea unguium, itrakonazol